Clinical efficacy and safety of robotic retroperitoneal lymph node dissection for testicular cancer: a systematic review and meta-analysis - Yuan, Yacheng; Zhang, Dawei; Ning, Yiping; Luo, Hengfeng; Qiu, Xiaolong; Tan, Yangyang; Li, Yuxiang; Yang, Xukai (Frontiers in Oncology, 2023)
Background: Retroperitoneal lymph node dissection (RPLND) is an effective treatment for testicular tumours. In recent years, with the development of robotics, many urological procedures performed via standard laparoscopy have been replaced by robots. Our objective was to compare the safety and efficacy of robotic retroperitoneal lymph node dissection (R-RPLND) versus Non-robotic retroperitoneal lymph node dissection (NR-RPLND) in testicular cancer. Methods: Pubmed, Embase, Scopus, Cochrane Library, and Web of Science databases were searched for literature on robotic surgery for testicular germ cell tumors up to April 2023. The statistical and sensitivity analyses were performed using Review Manager 5.3. Meta-analysis was performed to calculate mean difference (MD), odds ratio(OR), and 95% confidence interval (CI) effect indicators. Results: Eight studies with 3875 patients were finally included in this study, 453 with R-RPLND and 3422 with open retroperitoneal lymph node dissection (O-RPLND)/laparoscopic retroperitoneal lymph node dissection (L-RPLND). The results showed that R-RPLND had lower rates of intraoperative blood loss (MD = -436.39; 95% CI -707.60 to -165.19; P = 0.002), transfusion (OR = 0.06; 95% CI 0.01 to 0.26; P = 0.0001) , total postoperative complication rates (OR = 0.39; 95% CI 0.21 to 0.70; P = 0.002) , and length of stay (MD=-3.74; 95% CI -4.69 to -2.78; P<0.00001) . In addition, there were no statistical differences between the two groups regarding perioperative and oncological outcomes regarding total operative time, the incidence of postoperative complications grade ≥ III, abnormal ejaculation rate, lymph node yield, and postoperative recurrence rate. Conclusions: The R-RPLND and O-RPLND/L-RPLND provide safe and effective retroperitoneal lymph node dissection for testicular cancer. Patients with R-RPLND have less intraoperative bleeding, shorter hospitalization period, fewer postoperative complications, and faster recovery. It should be considered a viable alternative to O-RPLND/L-RPLND.